Multiparametric-MRI and Targeted Biopsies in the Management of Prostate Cancer Patients on Active Surveillance - Sandler, Kiri; Patel, Mausam; Lynne, Charles; Parekh, Dipen J.; Punnen, Sanoj; Jorda, Merce; Casillas, Javier; Pollack, Alan; Stoyanova, Radka (Frontiers in Oncology, 2015)
An important key to clinical management of prostate cancer patients is to determine early those who will benefit from primary treatment and are not good candidates for active surveillance (AS). We describe a 67-year-old gentleman with a long history of stable prostate-specific antigen (PSA) levels and a negative biopsy. After slight PSA rise and low volume Gleason score 6 biopsy, the patient was considered for primary treatment or AS. A multiparametric (MP)-MRI exam revealed a suspicious lesion in the anterior apex of the prostate. Biopsies were carried out on a 3D-ultrasound prostate biopsy system with MRI-fusion. The location of the target area was challenging and could have been missed using standard 12-core biopsy template. The pathology determined Gleason 3 + 4 disease in 30% of the core from this region. Consequently, the patient underwent radiotherapy (RT). MP-MRI was also used to follow the changes from pre- to post-RT.